Effects of Analyzed Calcium to Phosphorus Ratio on Growth Performance, Carcass Characteristics, Bone Mineralization, and Economics of 56- to 279-lb Pigs Fed Diets Containing Phytase - C. M. Vier; S. S. Dritz; M. D. Tokach; M. A. Gonçalves; U. A. Orlando; W. Cast; J. R. Bergstrom; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 1,215 barrows and gilts (PIC; 359 × Camborough) with an initial pen average body weight (BW) of 55.7 ± 2.06 lb were used in a 114-d growth trial to determine the effects of different analyzed calcium to analyzed phosphorus ratios on performance of growing-finishing pigs from 57- to 279-lb fed diets containing 1,000 phytase units. Pens of pigs were randomly assigned to 1 of 5 dietary treatments in a randomized complete block design with BW as a blocking factor. There were 9 replicate pens per treatment and 27 pigs per pen. The experimental diets were corn-soybean meal-based and were fed in 4 phases. The 5 dietary treatments were formulated to contain 0.75:1, 1.00:1, 1.25:1, 1.50:1, and 2.00:1 analyzed Ca:P ratios. The diets contained 1,000 phytase units (FYT) of Ronozyme Hiphos 2500 (DSM Nutritional Products, Inc., Parsippany, NJ) with assumed releasing values of 0.15% availableP(aP) and 0.132% standardized total tract digestibleP(STTD P). All the diets were formulated to contain adequate STTD P across the dietary treatments in all phases, which included the expected release of phytase. The treatments were achieved by increasing the amount of calcium carbonate at the expense of corn while maintaining monocalcium phosphate constant. Overall, increasing analyzed Ca:P ratio quadratically increased (P<0.05) average daily gain (ADG), final BW, and average daily feed intake (ADFI) (P<0.10). The greatest increase in these criteria was observed as the ratio increased from 0.75:1 to 1.50:1, with no improvement thereafter. Feed efficiency improved linearly (P<0.05) with increasing analyzed Ca:P ratio up to 2.00:1. For carcass characteristics, hot carcass weight (HCW) increased quadratically (P<0.05) as the analyzed Ca:P ratio increased from 0.75:1 to 1.50:1, and started to decrease thereafter. Percentage carcass yield decreased (quadratic,P<0.10) from 0.75:1 analyzed Ca:P ratio to 1.25:1, slightly increasing at higher ratios. Bone mineralization increased quadratically (P<0.05) with increasing analyzed Ca:P ratio. The greatest improvement in percentage bone ash was observed as analyzed Ca:P ratio increased from 0.75:1 to 1.25:1, with no further increase. Feed cost per pig increased linearly (P<0.05) with increasing analyzed Ca:P ratio. No evidence of differences (P>0.10) was observed for feed cost per pound of gain. Gain value per pig increased quadratically (P<0.05), with the greatest revenue observed for pigs fed diets with 1.50:1 analyzed Ca:P ratio. There was a marginal quadratic improvement (P<0.10) in income over feed cost (IOFC), with the highest income observed at 1.25:1 analyzed Ca:P ratio. The best fitting models for ADG, ADFI, feed efficiency, HCW, and bone ash were the quadratic polynomial (QP), linear, broken-line linear (BLL), QP, and BLL models, respectively. The maximum responses in ADG, feed efficiency, HCW, and bone ash were estimated at 1.63:1, 1.05:1, 1.11:1, and 1.25:1 analyzed Ca:P ratio, respectively. In conclusion, the estimated analyzed Ca:P ratio requirement for finishing pigs from 56- to 279-lb fed diets containing 1,000 phytase units and that were adequate in STTD P ranged from 1.05:1 to 1.63:1 to maximize growth rate, feed efficiency, HCW, and bone mineralization criteria.
Keywords: calcium; phosphorus; finishing pigs; phytase; bone ash